PENGARUH PENGALAMAN KERJA, SKEPTISME PROFESIONAL, DAN TIPE KEPRIBADIAN TERHADAP KEMAMPUAN AUDITOR DALAM PENGUNGKAPAN KECURANGAN (FRAUD) - Subiyanto, Bambang; Digdowiseiso, Kumba; Mandasari, Noviyanti (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to examine and analyze work experience, professional skepticism and personality types on the auditor's ability to disclose fraud. The type of data used is quantitative data with primary data sources. The population in this study were auditors who worked at the Public Accounting Firm (PAF) in Central Jakarta and South Jakarta. The statistical tool used to test this hypothesis is multiple regression with IBM SPSS Statistics 25. The data were obtained by distributing questionnaires to respondents and the data were processed as many as 138 questionnaires. These results indicate that of the 3 hypotheses, all data are supported by data. Based on the hypothesis test, the results show that work experience and professional skepticism have a positive effect on the ability of auditors to disclose fraud because high work experience causes auditors to be faster in assessing the risk of fraud and with high skepticism the auditor will seek more evidence to prove that the financial statements are free from all forms of cheating. Meanwhile, personality type has a negative effect on the ability of auditors to disclose fraud because each executive auditor is required in his profession to carry out his duties professionally.